2013
DOI: 10.1039/c3ra23181j
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel nanocarrier encapsulated recombinant IκBα as a novel anticancer protein therapeutics

Abstract: The NFkB overexpression triggers drug resistance in many types of cancer by up-regulating anti-apoptotic genes. IkBa, an endogenous protein and natural inhibitor of NFkB, blocks translocation of NFkB from cytoplasm to nucleus and thereby, sensitizes cancer cells to external stimuli. Herein, we have cloned a PCR amplified cDNA of IkBa, and expressed the recombinant GST tagged IkBa in Escherichia coli BL21 (DE3) cells. The recombinant GST-IkBa was purified by glutathione-agarose affinity chromatography and chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Also, the polymer NC composite could easily be synthesized in the form of hydrogel nanocarrier, by using PVA as the cross linker, which is favorable for cellular uptake. 27 The hydrogel could be then turned into a powder, which showed stable fluorescence, owing to the NCs, for more than a month. Further, the emission due to the NCs was useful for imaging mammalian cells by optical microscopy and more importantly to probe the cells by commercial flow cytometer, without having to use any other dye.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the polymer NC composite could easily be synthesized in the form of hydrogel nanocarrier, by using PVA as the cross linker, which is favorable for cellular uptake. 27 The hydrogel could be then turned into a powder, which showed stable fluorescence, owing to the NCs, for more than a month. Further, the emission due to the NCs was useful for imaging mammalian cells by optical microscopy and more importantly to probe the cells by commercial flow cytometer, without having to use any other dye.…”
Section: Introductionmentioning
confidence: 99%
“…The fluorescence of the composite was found to be sensitive to the pH of the medium, and the emission could be tuned reversibly according to the pH. Also, the polymer NC composite could easily be synthesized in the form of hydrogel nanocarrier, by using poly­(vinyl alcohol), PVA, as the cross-linker, which is favorable for cellular uptake . The hydrogel could be then turned into a powder, which showed stable fluorescence, owing to the NCs, for more than a month.…”
Section: Introductionmentioning
confidence: 99%
“…IkBa was cloned in the pGEM-T Easy vector (Promega) as described previously. 40 The IkBa gene was transferred from pGEM-T Easy to the pCINeo vector (Promega) by digestion with restriction enzymes followed by ligation. IkBa cloned in the pGEM-T Easy vector was digested with Eco RI (cutting site 5 0 GAATTC 3 0 ) and Spe I (cutting site 5 0 ACTAGT 3 0 ).…”
Section: Cloning Of Ikba In Mammalian Expression Vectormentioning
confidence: 99%
“…Studies have elaborated on the phenomenon of chemosensitization of cancer cells toward a conventional chemotherapeutic agent by overexpression of a relevant gene or addition of a therapeutic protein. , This fact has been exploited in this work, whereby the binding of protein to Chi-Au NC-Alg was found to considerably sensitize HeLa cells toward cisplatin. The MTT assay exhibited a sharp reduction in cell viability in the case of combination therapy (cisplatin with protein-NPs), as compared to that of only protein-NPs or only cisplatin treated cells (Figure A).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Recent material innovations have propagated a paradigm shift toward the unique concept of the codelivery of drug and therapeutic molecules conjugated to nanocarriers . Studies have revealed that these therapeutic molecules by themselves may not be toxic enough to eradicate cancer completely but that they may be used in combination with chemotherapy to help reduce the dosage of drugs and diminish their side effects. , Ligand-targeted NPs loaded with chemotherapeutic drugs are increasingly finding application in the remedy of cancer, with the common targets being receptors overexpressed by cancer cells, such as folate and transferrin receptors. However, even though aberrant upregulation of the Wnt pathway is one of the highlights in cancer, to date there has been no report documenting the targeting of the Wnt pathway with NPs for cancer therapy.…”
Section: Introductionmentioning
confidence: 99%